Synthesis of control laws, when aerostat is influenced by instructed disturbances - Абрамович, О.О.; Булавкіна, С.О.; Надсадна, О.І. (Proceedings of National Aviation University, 2010)
Aerostatic platforms are perspective project for securing mobile communication. Robust system should be synthesized for stabilizing. It can function in the following wide disturbance range: stratosphere wind (structure disturbance), parametric disturbance (unstructured disturbance). One of the way to solve the task is a -many-model approach. The appraisal of discrete system stability, which are influenced by disturbances, was made by the Kharytonov theorem.